MOHS MICROGRAPHIC SURGERY IN NON-MELANOMA SKIN CANCER - BEZERRA, THIAGO AUGUSTO ROCHETTI; Valiengo , Ana Graziela de Almeida; Pereira, Ingrid Adriana; Salustiano, Juliana Girardi Bruniera; Gomes, Maria Fernanda Hagemann; Bravo , Mariana Carrilho Soares; Soares, Veridiana Tasqueti Porto Rizzi; Oliveira , Maria Vitória Franco Alves de; Cannizzarro , Elizangela Vilela Caldas (Brazilian Journal of Implantology and Health Sciences, 2025)
Mohs Micrographic Surgery (MMS) is an advanced technique used to treat non- melanoma skin cancers, especially basal cell carcinoma and squamous cell carcinoma. This study presents a literature review on the application of MMS, highlighting its indications, benefits, limitations and recent advances. MMS offers high cure rates, often over 99% for primary tumors, while preserving as much healthy tissue as possible, making it the gold standard for lesions in critical areas such as the face, hands and genitals. The method combines precise tumor excision with intraoperative microscopic mapping, guaranteeing cancer cell-free margins and reducing the need for reinterventions. The review included studies addressing clinical outcomes, efficacy and comparison with other therapeutic modalities. The results confirm the superiority of MMS in high-risk, recurrent tumors or those with poorly defined margins, as well as its effectiveness in reducing complications and preserving functionality and aesthetics. However, limitations include the need for specialized infrastructure and trained staff, restricting its widespread implementation. It is concluded that MMS is a safe and effective approach, and it is essential to encourage its dissemination and to carry out new research to optimize its clinical application.